Implementation of Higher Order Thinking (HOTS) Based Assessment in the Subject of Islamic Religious Education (PAI) in Class 7 SMPN 1 Lebong Bengkulu - Dedi Damhudi; Deri Wanto (Journal of Educational Analytics, 2023)
Assessment is an instrument used to measure the success of a program. In the world of education there are many assessment models or instruments, one of which is a hots-based assessment. This study aims to describe the implementation of host-based assessment on PAI subjects at SMPN 1 Lebong. The research method used in this study is a qualitative research method. Data collection techniques were carried out by interviews, observation, and documentation. While data analysis used qualitative data analysis from Milles which included several stages, namely, data reduction, data presentation, and drawing conclusions. The results of the study show that in the implementation of host-based assessments on PAI subjects in class 7 SMPN 1 Lebong, it is carried out using various strategies. There are positive and negative impacts on students in implementing host-based assessments in class 7 SMPN 1 Lebong.